Steps towards Elimination of Obstetric Fistula in Bangladesh: Reflection from 2nd National Strategy for Obstetric Fistula 2017-2022 (Nepal Journal of Obstetrics and Gynaecology, 2018)
Aims: To see impact of second National Strategy for Obstetric Fistula 2017-2022 in BangladeshMethods: Under the supervision of The National Task Force on Obstetric Fistula of the Ministry of Health and Family Welfare, UNFPA supported the government in the development of the 2nd national strategy. A technical group developed the strategy and submitted to the Ministry of Health and Family Welfare for final approval. The second national obstetric fistula strategy 2017 – 2022 is a major step towards a fistula-free Bangladesh within a generation and reduces the burden of disease.Results: The strategy sets the vision for all girls born henceforth in Bangladesh will enjoy a life free from the risk of Obstetric Fistula and all cases of fistula will receive the highest quality of care enabling a high quality of life. Six directions set include prevention, improvement of services, quality treatment, psychosocial reintegration and rehabilitation, evidence generation and increase awareness. The set target aims to reach zero incidences of obstetric fistula by2022, reduce prevalence of repairable fistula cases by 90% and provide social safety nets and rehabilitation to 50% of all (repairable and incurable) cases of fistula between 2017 and 2022.Conclusions: Multi sectoral efforts needed under an effective coordination to operationalize the second strategy in Bangladesh.